PENINGKATAN KETERAMPILAN MENULIS TEKS DESKRIPSI MENGGUNAKAN METODE QUANTUM WRITING DENGAN MEDIA VIDEO PADA SISWA KELAS X SMK CINTA BUMI KHATULISTIWA TAHUN AJARAN 2016/2017 - Devee, Suzie Laxmy; Syambasril, Syambasril; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstactThe Background of this research is student?s writing descriptive text ability in SMK Cinta Bumi Khatulistiwa are under the minimum criteria. There were only 7 students who achieved the value of 75 which is the minimum criteria established by the school. The problem is because students are difficult to distinguish between descriptive text and exposition text. In addition students are also required to write descriptive text that makes students suppressed and afraid to write. The method of this research is descriptive method with qualitative research form. Sources of data in this research is teacher and 32 tenth grade students of SMK Cinta Bumi Khatulistiwa. The data is in the document in form lesson plan and the result of student?s test of writing descriptive text ability through quantum writing method. technique of the data collection are observation technique and measurement technique. The average number of values in writing descriptive text through quantum writing method using video as the media in the first cycle is 2347 or 73,3 and the second cycle increase 2501 or 78,0. It?s means quantum writing gave effect on student in SMK Cinta Bumi Khatulistiwa. Keywords: writing ability, descriptive text, quantum writing method